Potential Link Between Janus Kinase 2 Mutation and Renal Artery Stenosis Leading to Refractory Secondary Hypertension - A Case Report - Lakshmipriya V; Vanishree Murugavel; Jayaganesh (Dr. Annil Mahajan, 2024)
Polycythaemia vera (PV) is a rare BCR/ABL negative chronic myeloproliferative neoplasm characterized by increased red cell mass, splenomegaly and JAK2 V617 mutation in nearly all patients. The frequency of acquired Janus kinase 2 (JAK 2) V617 mutation is about 95% in PV patients. Herein, we report a case of renal artery stenosis leading to uncontrolled hypertension in a patient with PV having JAK2 V617F mutation, high haematocrit levels and erythrocytosis. A syndrome of refractory secondary hypertension, renal artery stenosis and erythrocytosis could be seen in the same patient. However, renovascular hypertension may be a thrombotic complication of primary erythrocytosis seen in PV patients and may lead to secondary erythrocytosis. Thus, patients with PV having JAK2 V617 mutation must be evaluated for thrombosis and optimally managed when hypertension coexist.